Geografia e Peregrinação / Geography and Pilgrimage - de Souza, José Arilson Xavier (Caderno de Geografia, 2018)
Refletir acerca da relação entre geografia e peregrinação é a intenção deste artigo. Tal relação é investigada à luz das dimensões espaço-culturais que marcam a vida dos homens peregrinos. Com efeito, as peregrinações são compreendidas como processos de raízes geográfico-sociais que relacionam espaços, tempos e indivíduos e contextualizados mundos de significados, desvelando, assim, uma espécie de geografia das peregrinações. Ao focar na prática das peregrinações a pé, a noção de busca pelo espaço sagrado é ainda privilegiada nas reflexões impostas. Palavras-chave: Geografia; Peregrinação: Geografia das Peregrinações. Abstract To reflect on the relationship between geography and pilgrimage is the intention of this article. The relation is investigated to the light of space-cultural dimensions that have been striking the life of pilgrim men. As an effect, the pilgrimages are understood as processes of geographical-social roots that relation spaces, times and individuals and several contextualized significances, exposing, like this, a kind of geography of pilgrimage. In focus in the pilgrimage practicals on foot, the notion of searching for the sacred space it is yet privileged in the imposed reflexions. Keywords: Geography; Pilgrimage; Geography of Pilgrimages.